2022
DOI: 10.1007/s00127-022-02387-8
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic disparities in the use of restrictive practices in adult mental health inpatient settings: a scoping review

Abstract: Purpose To identify and summarise extant knowledge about patient ethnicity and the use of various types of restrictive practices in adult mental health inpatient settings. Methods A scoping review methodological framework recommended by the JBI was used. A systematic search was conducted in APA PsycINFO, CINAHL with Full Text, Embase, PubMed and Scopus. Additionally, grey literature searches were conducted in Google, OpenGrey and selected websites, and the reference lis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
5

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 97 publications
1
15
0
5
Order By: Relevance
“…As shown in Table 2, research has been conducted mainly in general mental health settings, with only one study from forensic mental health. This distribution of settings was not surprising as it is supported by recent research analysis within restrictive practice use (Baker et al, 2021;Pedersen et al, 2022). However, people in forensic mental health are hospitalized in restrictive settings where the level of conflict and use of restrictive practices may be particularly high (Pedersen, 2020;Völlm & Nedopil, 2016).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…As shown in Table 2, research has been conducted mainly in general mental health settings, with only one study from forensic mental health. This distribution of settings was not surprising as it is supported by recent research analysis within restrictive practice use (Baker et al, 2021;Pedersen et al, 2022). However, people in forensic mental health are hospitalized in restrictive settings where the level of conflict and use of restrictive practices may be particularly high (Pedersen, 2020;Völlm & Nedopil, 2016).…”
Section: Discussionmentioning
confidence: 65%
“…Thus, these factors could either increase or decrease the probability of its use, indicating the risk of using rapid tranquillization without being based on professional clinical judgement. The risk is underpinned by its widespread use (Hu et al, 2019; Muir‐Cochrane, Grimmer, Gerace, et al, 2020; Raboch et al, 2010) and the reported risk factors associated with its use (Beames & Onwumere, 2021; Pedersen et al, 2022). Further research in this field is needed to ensure minimal and safe use and safety for all.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the exclusion of grey literature by the authors may have increased the risk of not finding all relevant studies and perspectives on the ethics of care in technology-mediated healthcare practices. As an example of the usefulness of grey literature searches, in a recent scoping review of research literature, nearly 50% of all included studies (16 out of 38) were identified through sources other than bibliographic databases [4].…”
Section: E T T E R T O T H E E D I T O R Enhancing Research Inclusion...mentioning
confidence: 99%
“…However, by lacking grey literature searches, the authors may have biased their findings towards a narrower range of sources. Like others [4], the authors' inclusion criteria focus on English-language literature. However, primarily research conducted in the Scandinavian and Northern American context was included, and the question is whether the topic is so contextspecific, as reported in the study, or whether it is possible to find relevant English-language literature in other contexts through grey sources.…”
Section: E T T E R T O T H E E D I T O R Enhancing Research Inclusion...mentioning
confidence: 99%